Hibiscus attenuates renovascular hypertension–induced aortic remodeling dose dependently: the oxidative stress role and Ang II/cyclophilin A/ERK1/2 signaling - ShamsEldeen, Asmaa Mohammed; Fawzy, Ahmed; Ashour, Hend; Abdel-Rahman, Marwa; Nasr, Hend Elsayed; Mohammed, Lina Abdelhady; Abdel Latif, Noha Samir; Mahrous, Amr M.; Abdelfattah, Shereen (Frontiers in Physiology, 2023)
The high levels of angiotensin II (Ang II) can modify the vascular tone, enhance vascular smooth muscle cells (VSMCs) proliferation and hypertrophy and increase the inflammatory cellular infiltration into the vessel wall. The old herbal nonpharmacological agent, Hibiscus (HS) has multiple cardioprotective impacts; thus, we investigated the role of HS extract in amelioration of renovascular hypertension (RVH)-induced aortic remodeling. Thirty-five rats (7/group) were randomly allocated into 5 groups; group: I: Control-sham group, and RVH groups; Π, III, IV, and V. The rats in RVH groups were subjected to the modified Goldblatt two-kidneys, one clip (2K1C) for induction of hypertension. In group: II, the rats were left untreated whereas in group III, IV, and V: RVH-rats were treated for 6 weeks with low dose hibiscus (LDH), medium dose hibiscus (MDH), and high dose hibiscus (HDH) respectively. We found that the augmented pro-contractile response of the aortic rings was ameliorated secondary to the in-vivo treatment with HS dose dependently. The cyclophilin A (CyPA) protein levels positively correlated with the vascular adhesion molecule-1 (VCAM-1) and ERK1/2, which, in turn, contribute to the reactive oxygen species (ROS) production. Daily HS intake modified aortic renovation by enhancing the antioxidant capacity, restraining hypertrophy and fibrosis, downregulation of the metastasis associated lung adenocarcinoma transcript (MALAT1), and cyclophilin A (CyPA)/ERK1/2 levels. Thus, adding more privilege for the utilization of the traditional herbal extracts to attenuate RVH-induced aortopathy.